2019
DOI: 10.5811/cpcem.2018.11.39667
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Treatment of Neuroleptic Malignant Syndrome Induced by Antipsychotic Monotherapy Using Dantrolene

Abstract: Neuroleptic malignant syndrome (NMS) is a rare but potentially fatal complication resulting from neuroleptic drug therapy. Presentation of NMS can vary, and diagnosis relies primarily upon medical history and symptomatology. Due to the potential delay in diagnosis, emergency physicians should remain vigilant in recognizing the symptoms of NMS and be prepared to initiate immediate treatment following diagnosis. Dantrolene, which has been used for spasticity and malignant hyperthermia, has been reported as a pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Oral dantrolene is approved by the FDA for the treatment of chronic muscle spasticity. 15 Dantrolene has also been used off license for treating muscle spasms and hyperthermia unresponsive to conventional therapies in neuroleptic malignant syndrome, 16 MDMA intoxication, 17 and heat stroke, 9,18 and for treating muscle symptoms or recurrent rhabdomyolysis in MHS patients carrying pathogenic RYR1 variants. [19][20][21] However, a black box warning of liver failure was included in the package insert after 2% of patients (19/1044) who received dantrolene developed liver injury and 3 patients died.…”
Section: Discussionmentioning
confidence: 99%
“…Oral dantrolene is approved by the FDA for the treatment of chronic muscle spasticity. 15 Dantrolene has also been used off license for treating muscle spasms and hyperthermia unresponsive to conventional therapies in neuroleptic malignant syndrome, 16 MDMA intoxication, 17 and heat stroke, 9,18 and for treating muscle symptoms or recurrent rhabdomyolysis in MHS patients carrying pathogenic RYR1 variants. [19][20][21] However, a black box warning of liver failure was included in the package insert after 2% of patients (19/1044) who received dantrolene developed liver injury and 3 patients died.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, dantrolene is a central and peripheral muscle relaxant widely used for patients with MS. Nevertheless, similarly to cyproheptadine, studies have failed to show its efficacy [17]. For these reasons, after discontinuing duloxetine and re-starting all her antiparkinson medication, we treated our patient only with supportive measures.…”
Section: Featuresmentioning
confidence: 99%
“…This mechanism has mainly been studied in skeletal muscle; however, studies in cultured neurons have shown that dantrolene can block up to 70% of the Ca 2+ rise coming from the endoplasmic reticulum because of NMDAr activation, as well as reducing neuronal apoptosis [115]. The dose required for the treatment of malignant hyperthermia and neuroleptic malignant syndrome is similar, oscillating between 1 and 2.5 mg/kg for neuroleptic malignant syndrome and 2.5 mg/kg for malignant hyperthermia [144]. As for the dosage used to achieve the desired effect in TBI, studies have shown how an interval from 10-100 µM of dantrolene administered during the appropriate therapeutic window will target and reduce excitotoxicity.…”
Section: Dantrolenementioning
confidence: 99%